Association of fasting glucose levels with incident atherosclerotic cardiovascular disease: An 8‐year follow‐up study in a Chinese population: 中国人群空腹血糖水平与动脉粥样硬化性心血管疾病发病的关系:一项为期8年的随访研究. (16th March 2016) - Liu, Fangchao; Yang, Xueli; Li, Jianxin; Cao, Jie; Chen, Jichun; Li, Ying; Liu, Xiaoqing; Zhao, Liancheng; Shen, Chong; Yu, Ling; Huang, Jianfeng; Gu, Dongfeng
Abstract: Background: Identification of the population at high risk of developing atherosclerotic cardiovascular disease (ASCVD) is critical for its prevention. The aim of the present study was to evaluate the use of fasting blood glucose (FBG) to predict ASCVD. Methods: In all, 18 610 participants, aged 35–74 years at enrollment, were included in this prospective study. Baseline information was collected using a standardized questionnaire, physical examinations, and laboratory tests. During follow‐up, disease status and vital information were updated. Cox proportional hazards regression analysis was used to estimate associations, with normal FBG (70–99 mg/dL) as the reference group. Anthropometric measurements, socioeconomic status, and conventional cardiovascular risk factors were included in the multivariate‐adjusted model. Results: After 7.8 years follow‐up (145 223 person‐years), there were 519 cases of ASCVD. The multivariate‐adjusted hazard ratios (HR), with 95% confidence intervals (CI), for ASCVD in patients with low FBG (<70 mg/dL), impaired fasting glucose (IFG; 100–125 mg/dL), and diabetes (≥126 mg/dL, use of antidiabetic medication and/or self‐report) were 1.35 (0.84, 2.15), 1.02 (0.81, 1.27), and 1.68 (1.26, 2.23), respectively. Although IFG was associated with the development of diabetes (multivariate‐adjusted HR 3.67; 95% CI 3.20, 4.21), it was only associated with incident ASCVD in the univariate model (HR 1.52; 95% CI 1.23, 1.88). The association of diabetes with coronary heart disease was more pronounced than that with stroke. Gender and residential differences were also identified. Conclusions: In the present study, IFG was associated with the development of diabetes but not incident ASCVD. Prevention strategies to reduce the development of diabetes in people with IFG are critical to improve cardiovascular health. Highlights: Diabetes other than impaired fasting glucose was associated with increased risk of incident ASCVD after 7.8 years follow‐up among 18 610 participants. Impaired fasting glucose increased the risk of developing diabetes. Prevention strategy on reducing incidence of diabetes in persons with impaired fasting glucose is critical to improve cardiovascular health status. Kaplan‐Meier curves of atherosclerotic cardiovascular disease (ASCVD) event‐free survival of participants according to fasting (serum) glucose groups. LFG, low fasting glucose; NFG, normal fasting glucose; IFG, impaired fasting glucose. Values across the bottom of the graph show the number of subjects at risk at each time point.